Fabry disease: an advance in the diagnostic laboratory for recognition of female carriers - Giner Ayala, Alicia (2013)
Fil: Giner Ayala, Alicia. Universidad Nacional de Córdoba. Facultad de Ciencias Médicas. Centro de Estudio de las Metabolopatías Congénitas; Argentina.